TRANSFORMASI NILAI BUDAYA DALAM MEMBANGUN AKUNTABILITAS ORGANISASI PEMERINTAH DAERAH STUDI ETNOGRAFI KRITIS AKULTURASI - Fransiskus Randa; Oktavianus Pasoloran (Jurnal Aplikasi Akuntansi, 2023)
This research was conducted to transform local cultural values ​​in building local government organizational accountability. The object of research is the local government organization of Tana Toraja. The determination of the research location is based on the existence of local culture which is still maintained by the local community. This study uses a postmodern paradigm with a critical acculturation ethnographic method. The research results transform cultural values, namely tallu bakana and the role of the tongkonan as an element of leadership and an element of governance. An organizational leader with the value of tallu bakana implies that an organizational leader must have courage, knowledge and wisdom. In the aspect of organizational governance, placing the organization as a pillar that is able to accommodate all stakeholder interests and resolve problems in a deliberative and amicable way